Enhancing students’ science process skills through macrozoobenthos-based worksheets: An inventory study at Rancabuaya Beach, West Java - Tri Wahyu Agustina; Maratus Solikha; Umar Rizky; Astri Yuliawati (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
This study aims to increase students’ science process skills (SPS) using student worksheets based on the results of the macrozoobenthos inventory at Rancabuaya Beach, West Java. This research was conducted in the even semester of the 2024/2025 academic year at a university in Bandung, West Java. This study employed a quasi-experimental pretest-posttest control group design with purposive sampling of 44 students enrolled in the ecology practicum course. SPS improvement was assessed using the N-Gain criterion for science process skills improvement, encompassing seven indicators: observing, classifying, interpreting, planning experiments, using tools and materials, applying concepts, and communicating. The results show that in the experimental class, SPS increased substantially, with an average N-Gain of 0.79, which was higher than in the control class (0.64, moderate). The most substantial increase was in planned experiments and in the use of tools and materials, with N-Gain 0.85, while communication showed the lowest increase with N-Gain 0.75. These results show that the experimental class experienced a significant increase in SPS indicators with student worksheets integrated with the local macrozoobenthos inventory. The implications of this research expand knowledge on the importance of incorporating local biodiversity in biology learning to improve science process skills, enrich learning media innovations, and provide a theoretical and practical foundation for the development of contextual science education.